Mutations in SLC34A3/NPT2c Are Associated with Kidney Stones and Nephrocalcinosis - Dasgupta, Debayan (American Society of Nephrology, 2014)
Compound heterozygous and homozygous (comp/hom) mutations in solute carrier family 34, member 3 (SLC34A3), the gene encoding the sodium (Na(+))-dependent phosphate cotransporter 2c (NPT2c), cause hereditary hypophosphatemic rickets with hypercalciuria (HHRH), a disorder characterized by renal phosphate wasting resulting in hypophosphatemia, correspondingly elevated 1,25(OH)(2) vitamin D levels, hypercalciuria, and rickets/osteomalacia. Similar, albeit less severe, biochemical changes are observed in heterozygous (het) carriers and indistinguishable from those changes encountered in idiopathic hypercalciuria (IH). Here, we report a review of clinical and laboratory records of 133 individuals from 27 kindreds, including 5 previously unreported HHRH kindreds and two cases with IH, in which known and novel SLC34A3 mutations (c.1357delTTC [p.F453del]; c.G1369A [p.G457S]; c.367delC) were identified. Individuals with mutations affecting both SLC34A3 alleles had a significantly increased risk of kidney stone formation or medullary nephrocalcinosis, namely 46% compared with 6% observed in healthy family members carrying only the wild-type SLC34A3 allele (P=0.005) or 5.64% in the general population (P<0.001). Renal calcifications were also more frequent in het carriers (16%; P=0.003 compared with the general population) and were more likely to occur in comp/hom and het individuals with decreased serum phosphate (odds ratio [OR], 0.75, 95% confidence interval [95% CI], 0.59 to 0.96; P=0.02), decreased tubular reabsorption of phosphate (OR, 0.41; 95% CI, 0.23 to 0.72; P=0.002), and increased serum 1,25(OH)(2) vitamin D (OR, 1.22; 95% CI, 1.05 to 1.41; P=0.008). Additional studies are needed to determine whether these biochemical parameters are independent of genotype and can guide therapy to prevent nephrocalcinosis, nephrolithiasis, and potentially, CKD.